2010
DOI: 10.1007/s11259-010-9359-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of synonymous codon usage in foot-and-mouth disease virus

Abstract: In this study, we calculate the relative synonymous codon usage (RSCU) values and codon usage bias (CUB) values to carry out a comparative analysis of codon usage pattern for open reading frames (ORFs) among 85 samples which belong to all seven serotypes of foot-and-mouth disease virus (FMDV). Although the degree of CUB for ORFs is a relatively slight, there is a significant variation for CUB among different serotypes, which is mainly determined by codon usage pattern depending on RSCU. By comparison with RSCU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…In general, previous reports have indicated that many viruses, including foot-andmouth disease viruses, influenza A virus subtype H5N1, severe acute respiratory syndrome Coronavirus (SARSCoV), and human bocavirus, preferentially use codons ending in C or G (Zhao et al, 2008;Zhou et al, 2010). However, in the case of the EV71 virus, only a few studies have been performed on the synonymous codon usage pattern influencing its evolution.…”
Section: Discussionmentioning
confidence: 99%
“…In general, previous reports have indicated that many viruses, including foot-andmouth disease viruses, influenza A virus subtype H5N1, severe acute respiratory syndrome Coronavirus (SARSCoV), and human bocavirus, preferentially use codons ending in C or G (Zhao et al, 2008;Zhou et al, 2010). However, in the case of the EV71 virus, only a few studies have been performed on the synonymous codon usage pattern influencing its evolution.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the pattern of relative synonymous codon usage (RSCU) without the influence of amino acid composition among all samples, the RSCU values of codons in each ORF of NDV, H5N2 and DHV were calculated according to the formula of previous reports [31,32].…”
Section: Composition Analysis Of Coding Region Of 31 Ndv Strainsmentioning
confidence: 99%
“…Additionally, there is a simple method that supposes that statistically equal and random usage of all available synonymous codons is the "neutral point" (RSCU 0 = 1.00) for the development of serotype-specific codon usage (Zhou et al, 2010). CUB:…”
Section: Analysis Of Codon Usage Biasmentioning
confidence: 99%
“…It is accepted that information on protein sequences and the formation of codon usage bias (CUB) arises from the non-randomness of nucleotide compositions (Lloyd and Sharp, 1992;Xie and Ding, 1998). In general, translation selection and compositional constraints under mutational pressure are thought to be major factors accounting for codon usage variation among genomes in microorganisms (Karlin and Mrázek, 1996;Lesnik et al, 2000;Zhou et al, 2006, Zhou et al, 2010. In some microorganisms, compared with translation selection in nature, mutation pressure plays an important role in the synonymous codon usage pattern (Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%